ANALISIS IMPLEMENTASI DANA DESA DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT DESA MUNGKIN KECAMATAN ORONG TELU - Binar Dwiyanto Pamungkas; Vivin Fitryani; Andi Saputra (Jurnal Ekonomi & Bisnis, 2021)
This study aims to describe and explain the implementation of village fund management in improving village community empowerment, perhaps in the Orong Telu sub-district. This type of research is descriptive qualitative research. The types of data used are primary data and secondary data. The technique used to collect data is through observation, interviews and documentation. Informants in this study were the village head, head of finance, head of welfare, head of BPD, head of youth organization and community beneficiaries of village funds. The data were analyzed using Miles Huberman's theory. The results of this study indicate that the management of village funds in the Possi Village, starting from planning, implementation, administration, to reporting and accountability is carried out properly and transparently. For the realization of village funds in the Possibility Village in the field of physical development in the form of road and agricultural infrastructure development, while in the field of empowerment in the form of, Socialization and Technical Guidance, Equity Participation in Village Owned Enterprises (BUMDes), PKK and Posyandu Activities, Social Empowerment, Direct Cash Assistance Funds Villages (BLTDD) and Covid-19 Prevention and Handling.